Market liberalization: Price dispersion, price discrimination and consumer search in the German electricity markets - Klaus Gugler; Sven Heim; Maarten C. W. Janssen; Mario Liebensteiner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
We study how consumer search affects pricing in markets with incumbents and entrants using panel data on German electricity retail markets. Consumers observe the baseline price of the incumbent and decide whether or not to search. Incumbent providers can price discriminate between searching and loyal consumers. Empirically we show that local incumbents increase their baseline rate while entrants decrease their tariffs if consumer search increases. Moreover, the incumbent price discriminates more strongly in markets with more consumer search. Using a theoretical model, we show that these pricing patterns are consistent with the strategic interaction of profit-maximizing firms.
Keywords: D43; D83; L11; L13; Q40; 330; Search; Price Dispersion; Price Discrimination; Electricity